Immunoregulatory Effects of Porcine Plasma Protein Concentrates on Rat Intestinal Epithelial Cells and Splenocytes - Cristina Hernández-Chirlaque; Carlos J. Aranda; Borja Ocón; Javier Polo; Olga Martínez-Augustin; Fermín Sánchez de Medina (Animals, 2021)
Serum protein concentrates have been shown to exert in vivo anti-inflammatory effects. Specific effects on different cell types and their mechanism of action remain unraveled. We aimed to characterize the immunomodulatory effect of two porcine plasma protein concentrates, spray dried serum (SDS) and an immunoglobulin concentrate (IC), currently used as animal nutritional supplements with established in vivo immunomodulatory properties. Cytokine production by the intestinal epithelial cell line IEC18 and by primary cultures of rat splenocytes was studied. The molecular pathways involved were explored with specific inhibitors and gene knockdown. Our results indicate that both products induced GROα and MCP-1 production in IEC18 cells by a MyD88/NF-κB-dependent mechanism. Inhibition of TNF production was observed in rat primary splenocyte cultures. The immunoglobulin concentrate induced IL-10 expression in primary splenocytes and lymphocytes. The effect on TNF was independent of IL-10 production or the stimulation of NF-kB, MAPKs, AKT, or RAGE. In conclusion, SDS and IC directly regulate intestinal and systemic immune response in murine intestinal epithelial cells and in T lymphocytes and monocytes.